Iditarod race - Hansen, Grace (Minneapolis, Minnesota : Abdo Kids Jumbo is an imprint of Abdo Kids, 2023)
Learn all about the history and cultural significance that the exciting Iditarod race event holds around the world today. This title is complete with historical and modern photographs, as well as a glossary and a closer look at the rules for mushers and their dog teams.
The Iditarod trail sled dog race -- History -- The race and events -- Big winners -- Some Iditarod race rules.
Includes index.
3.7
K-3
790L
Some copies purchased with funds from an OASL Connie Hull Mini-Grant, Mt. View 2024
Keywords: Sled dog racing -- Alaska -- Juvenile literature; Alaska -- Juvenile literature; Festivals -- Juvenile literature; Sled dog racing -- Alaska; Alaska; Festivals